Economic Effects and Structural Determinants of Capital Controls - Grilli, Vittorio (IMF Working Papers; Working Paper ;, 1995)
This paper studies determinants and effects of capital controls using a panel of 61 developed and developing countries. The results suggest that capital account restrictions are more likely to be in place in countries with low income, a large share of government, and where the central bank is not independent. Other determinants of controls include the exchange rate regime, current account imbalances and the degree of openness of the economy. We also find that capital controls and other foreign exchange restrictions are associated with higher inflation and lower real interest rates. We do not find any robust correlation between our measures of controls and the rate of growth, although there is evidence that countries with large black market premia grow more slowly.